Rapid Preparation of Biosorbents with High Ion Exchange Capacity from Rice Straw and Bagasse for Removal of Heavy Metals - Supitcha Rungrodnimitchai (The Scientific World Journal)
This work describes the preparation of the cellulose phosphate with high ion exchange capacity from rice straw and bagasse for removal of heavy metals. In this study, rice straw and bagasse were modified by the reaction with phosphoric acid in the presence of urea. The introduced phosphoric group is an ion exchangeable site for heavy metal ions. The reaction by microwave heating yielded modified rice straw and modified bagasse with greater ion exchange capacities (∼3.62 meq/g) and shorter reaction time (1.5–5.0 min) than the phosphorylation by oil bath heating. Adsorption experiments towards Pb2+, Cd2+, and Cr3+ ions of the modified rice straw and the modified bagasse were performed at room temperature (heavy metal concentration 40 ppm, adsorbent 2.0 g/L). The kinetics of adsorption agreed with the pseudo-second-order model. It was shown that the modified rice straw and the modified bagasse could adsorb heavy metal ions faster than the commercial ion exchange resin (Dowax). As a result of Pb2+ sorption test, the modified rice straw (RH-NaOH 450W) removed Pb2+ much faster in the initial step and reached 92% removal after 20 min, while Dowax (commercial ion exchange resin) took 90 min for the same removal efficiency.